Upaya Kegiatan Ekstrakurikuler Hadrah Dalam Membentuk Akhlakul Karimah Peserta Didik Di MTSN 1 Bengkalis - Ramadhan, Firly; Sufia, Neng; Fadilla, Nadia (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
The purpose of this study was to find out how the extracurricular activities outside the classroom take the form of Hadrah, which emphasizes the Akhlakul Karimah values of MTsN 1 Bengkalis students. This study uses a qualitative method with a descriptive approach. The basic group of this study consisted of coaches, trainers and students totaling 11 people, the sample in this study was 5 people. Data collection techniques used in this study were observation, interviews and documentation. The data analysis technique used in this study is the Miles and Huberman model, namely. Data Reduction, Data Presentation and Conclusion/Review. The results of this study indicate that activities outside the Hadrah class tend to form Akhlakul Karimah students at MTsN 1 Bengkalis which is marked by a change in the personality of each student consisting of students becoming more disciplined, responsible, polite and more disciplined. respect teacher. good relations and good social relations between the teacher and his friends